All-inorganic perovskite CsPbIBr2 thin film, preparation method and battery
By using two-dimensional single crystal material as nucleation seeds in perovskite film preparation, the problem of crystallization disorder of wide-bandgap perovskite film is solved, and the uniformity and electrical performance of the film are improved.
Patent Information
- Application Number
- CN202411877978.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-08
AI Technical Summary
During the crystallization process, all-inorganic wide-bandgap perovskite films are prone to excessive local Br content due to external temperature and other factors, resulting in advance crystallization, uneven film formation, disordered crystal plane orientation, poor film quality and easy phase separation.
A uniform all-inorganic perovskite CsPbIBr2 thin film was prepared by spin-coating the CsPbIBr2 precursor solution and annealing.
Through the assisted growth of two-dimensional single crystal materials, the nucleation barrier is reduced, the growth process of perovskites is extended, the uniformity of perovskite film and the regulation of crystal plane orientation is achieved, and the electrical properties of the film are improved.
Smart Images

Figure CN119774890A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite batteries, and in particular relates to an all-inorganic perovskite CsPbIBr2 film, a preparation method and a battery. Background Art
[0002] Traditional fossil energy is becoming increasingly depleted, and energy demand is increasing day by day. It is urgent to find new clean energy. Perovskite has become the fastest-growing new photovoltaic cell material in recent years due to its excellent light absorption and carrier transport properties. At the same time, the perovskite band gap is adjustable and the wide band gap semi-transparent property makes it applicable to photovoltaic building integrated photovoltaic (BIPV) photovoltaic glass.
[0003] In the process of preparing inorganic perovskite thin films, they are usually left to stand for a period of time after spin coating to allow the halogen ions in the liquid film state to spread evenly on the substrate. Wide-bandgap perovskites contain a large proportion of Br elements, and the external temperature and other factors can easily cause excessive local Br content during the crystallization process, leading to premature crystallization. The difference in the solubility of the two halogens during the crystallization process leads to uneven film formation, disordered crystal plane orientation, and ultimately a film with poor film quality and prone to phase separation. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an all-inorganic perovskite CsPbIBr2 film, a preparation method and a battery to solve the technical problem of crystal disorder of all-inorganic wide-bandgap perovskite.
[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing an all-inorganic perovskite CsPbIBr2 film, comprising the following steps:
[0006] S1, CsI and PbBr2 are mixed and dissolved in an organic solvent at a mass ratio of 200-300:300-400, and then filtered to obtain a CsPbIBr2 precursor solution;
[0007] S2. Spin-coat the CsPbIBr2 precursor solution onto the substrate, followed by annealing to obtain an all-inorganic perovskite CsPbIBr2 film.
[0008] On the basis of the above technical solution, the present invention can also be improved as follows:
[0009] Furthermore, the temperature at which S1 is dissolved is 55-65°C.
[0010] Furthermore, the filter membrane used for filtration is a PTFE membrane with a diameter of 0.2-0.25 μm.
[0011] Furthermore, the spin coating step is: first spin coat the CsPbIBr2 precursor solution at a rotation speed of 450-550rpm / s for 3-8s, and then spin coat at a rotation speed of 2000-3000rpm / s for 50-70s.
[0012] Furthermore, the annealing step is: placing the spin-coated material in a protective atmosphere, first annealing at 25-35°C for 50-70s, and then annealing at 130-170°C for 8-12min to obtain an all-inorganic perovskite CsPbIBr2 film.
[0013] The invention also discloses a fully inorganic perovskite CsPbIBr2 film prepared by the preparation method.
[0014] The invention also discloses the application of the all-inorganic perovskite CsPbIBr2 film in the preparation of the all-inorganic perovskite battery.
[0015] On the basis of the above technical solution, the present invention can also be improved as follows:
[0016] Further, the preparation steps of the all-inorganic perovskite battery are:
[0017] A1, cleaning the conductive substrate, and then preparing a ZnO electron transport layer on the conductive substrate;
[0018] A2. Prepare a two-dimensional single crystal material, and deposit the two-dimensional single crystal material on the surface of the ZnO electron transport layer to form a two-dimensional material seed layer (B2PbI4);
[0019] A3, preparing an all-inorganic perovskite CsPbIBr2 film on the surface of the two-dimensional material seed layer to obtain an ITO / ZnO / CsPbIBr2 film;
[0020] A4, preparing a Spiro-OMeTAD hole transport layer on the surface of the all-inorganic perovskite CsPbIBr2 film to obtain a substrate to be evaporated;
[0021] A5. Evaporate metal as an electrode on the surface of the Spiro-OMeTAD hole transport layer of the substrate to be evaporated to produce a battery device.
[0022] Furthermore, A1 is specifically:
[0023] A101, rinse the conductive surface of the conductive substrate, then ultrasonicate in water, acetone, anhydrous ethanol and isopropanol for 20-30 minutes, then blow dry with nitrogen, and finally ultrasonicate in a UV ozone environment for 15-25 minutes to obtain a pretreated ITO substrate; the power of each ultrasonication is 30-50KHz;
[0024] A102, uniformly mix Zn(CH3COO)2·2H2O and ethanolamine in dimethyl glycol, filter, and obtain a ZnO precursor solution; the ratio of Zn(CH3COO)2·2H2O, ethanolamine and dimethyl glycol is 80-120 mg: 25-30 μL: 950-1000 μL;
[0025] A103. Spin-coat the ZnO precursor solution on the pretreated ITO substrate at a rotation speed of 3500-4500 rpm / s for 25-35 seconds, and then anneal at 180-220° C. for 25-35 minutes to obtain an ITO / ZnO substrate.
[0026] Furthermore, A2 is specifically:
[0027] A201, PbO powder, hydroiodic acid and hypophosphorous acid solution are mixed, and then stirred at 80-100°C for 25-35 minutes to obtain solution 1; the ratio of PbO powder, hydroiodic acid and hypophosphorous acid is 0.5-1.5 mmol: 0.5-1.5 mL: 180-220 μL;
[0028] A202, mixing benzylamine solution, hydroiodic acid and hypophosphorous acid solution at a volume ratio of 180-210:900-1100:150-250 at 45-55° C. to obtain solution 2;
[0029] A203, solution 1 and solution 2 are mixed at a volume ratio of 1-2:1-2 at 45-55°C, followed by adding hydroiodic acid and hypophosphorous acid solutions, and then the temperature is raised to 110-130°C and stirred until the solution becomes transparent, and finally cooled to room temperature to obtain a two-dimensional single crystal material; the volume ratio of solution 1, solution 2, hydroiodic acid and hypophosphorous acid solution is 180-210:180-210:900-1100:150-250;
[0030] A204. Dissolve the two-dimensional single crystal material in an organic solvent, and then spin-coat it on the surface of the ZnO electron transport layer of the ITO / ZnO substrate at a rotation speed of 2500-3500 rpm / s for 25-35s to obtain a two-dimensional material seed layer (B2PbI4).
[0031] Further, A4 is specifically as follows: 2,2',7,7'-tetrakis[N,N-diphenylamino]-9,9'-spirobifluorene (Spiro-OMeTAD) is dissolved in a chlorobenzene solution, followed by standing for 1-2 hours, and then 4-tert-butylpyridine (TBP), a lithium salt solution and a cobalt salt solution are added, stirred evenly and continued to stand for 2-3 hours, filtered, and the filtrate is dropwise coated on the surface of the all-inorganic perovskite CsPbIBr2 film, and rotated at a speed of 4500-5500 rpm for 25-35 seconds to obtain a substrate to be evaporated; the ratio of Spiro-OMeTAD, TBP, lithium salt solution and cobalt salt solution is 70-75 mg: 25-30 μL: 15-20 μL: 25-30 μL.
[0032] Furthermore, the lithium salt solution is prepared by dissolving lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in acetonitrile at a ratio of 500-550 mg:0.5-1.5 mL, and the cobalt salt solution is prepared by dissolving tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt(III)tris(N-[(trifluoromethyl)sulfonyl]methanesulfonamide) (Co(III)-TFSI) in acetonitrile at a ratio of 250-350 mg:0.5-1.5 mL.
[0033] Further, A5 is specifically as follows: the substrate to be evaporated and the sample are placed into the chamber, and the mechanical pump and the molecular pump are evacuated to 10 -4 Pa, first 0.05- The deposition rate was then increased to 0.25- Until the total thickness of the deposited layer is 45-55nm, finally 0.45- The deposition rate is evaporation until the total thickness of the deposited layer is 65-75nm.
[0034] The beneficial effects of the present invention are:
[0035] (1) Heterogeneous nucleation: All-inorganic perovskites with high Br content are prone to growth and crystal disorder. Two-dimensional materials can be used as heterogeneous nucleation seeds for perovskites, reducing the nucleation barrier, making the crystallization process smoother and prolonging the perovskite growth process, thus obtaining a uniform perovskite film.
[0036] (2) Crystal plane regulation: Two-dimensional single crystals are microscopic layered materials with orientation-advantage characteristics. After deposition, two-dimensional single crystals maintain their original microstructural state. During the epitaxial wide-bandgap perovskite process, they can induce the growth of specific crystal planes of perovskite, making the (100) crystal plane and (110) crystal plane close to the ideal 1:1 ratio, thus achieving the regulation of the perovskite crystal plane orientation and ratio.
[0037] (3) Improved electrical performance: During the carrier transport process, secondary phases and defects will capture electron holes, increasing non-radiative recombination. The thin films prepared by two-dimensional single crystal induction have greatly improved carrier transport speed and diffusion length. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 UV-visible absorption spectra of two-dimensional single crystals B2PbI4 and T2PbI4;
[0039] Figure 2 XRD spectra of two-dimensional single crystal B2PbI4 and T2PbI4;
[0040] Figure 3 Schematic diagram of the film formation process of the traditional thin film growth method;
[0041] Figure 4 Schematic diagram of the film forming process of the method of the present invention;
[0042] Figure 5 Quasi-in-situ XRD characterization of traditional thin film growth method under low temperature annealing state;
[0043] Figure 6 Quasi-in-situ XRD characterization of two-dimensional single crystal assisted growth film formation under low temperature annealing state;
[0044] Figure 7 GIWAXS image of the thin film obtained by the traditional film forming method;
[0045] Figure 8 GIWAXS image of the thin film obtained by 2D single crystal assisted growth;
[0046] Fig. 9 Comparison of the (100):(110):(111) crystal plane ratios of the two films in GIWAXS testing;
[0047] Fig.10 This is a comparison chart of the TPC test results of the device;
[0048] Fig.11 This is a comparison chart of TPV test results of the device;
[0049] Fig.12 This is a comparison chart of the IMPS test results of the device;
[0050] Fig.13 This is a comparison chart of the IMVS test results of the device;
[0051] Fig.14 The JV curve comparison chart of the device. DETAILED DESCRIPTION
[0052] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
[0053] Example 1
[0054] A method for preparing an all-inorganic perovskite CsPbIBr2 film comprises the following steps:
[0055] S1. Mix and dissolve 259.8 mg CsI and 367.01 mg PbBr2 in 1 mL DMSO solution at 60 °C. After the solution cools to room temperature, filter it through a PTFE membrane with a filter diameter of 0.22 μm to obtain a completely clear CsPbIBr2 precursor solution.
[0056] S2. Spin coat 40 μL of CsPbIBr2 precursor solution on an ITO / ZnO conductive glass substrate, first at 500 rpm / s for 5 seconds, and then at 2500 rpm / s for 60 seconds; anneal the spin-coated material in a nitrogen atmosphere at 30°C for 60 seconds, and then at 150°C for 10 minutes to obtain an all-inorganic perovskite CsPbIBr2 thin film.
[0057] The preparation steps of all-inorganic perovskite cells are:
[0058] A1. Cleaning the ITO transparent conductive glass substrate, and then preparing a ZnO electron transport layer on the ITO transparent conductive glass substrate; specifically:
[0059] A101. Wipe the etched 16mm*16mm ITO transparent conductive glass with absorbent cotton dipped in detergent water, and rinse the conductive surface. Then, place it in water, acetone, anhydrous ethanol and isopropanol for 25 minutes, blow it dry with nitrogen, and finally ultrasonicate it in ultraviolet ozone environment for 20 minutes to improve the surface wettability, so as to obtain a pretreated ITO substrate; the power of each ultrasonication is 40KHz;
[0060] A102, 100 mg Zn(CH3COO)2·2H2O and 28.29 μL ethanolamine were uniformly mixed in 973 μL dimethyl glycol, and then filtered through a polyethersulfone (PES) filter with a filter diameter of 0.22 μm to obtain a ZnO precursor solution;
[0061] A103, spin coating the ZnO precursor solution on the pretreated ITO substrate at a speed of 4000 rpm / s for 30 seconds, and then annealing at 200° C. for 30 minutes to obtain an ITO / ZnO substrate;
[0062] A2. Prepare a two-dimensional single crystal material, and deposit the two-dimensional single crystal material on the surface of the ZnO electron transport layer to form a two-dimensional material seed layer; specifically:
[0063] A201, 1 mmol of PbO powder, 1 mL of 57 wt% hydroiodic acid solution and 200 μL of hypophosphorous acid solution were mixed, and then stirred at 90° C. for 30 min to obtain solution 1;
[0064] A202, 198 μL of benzylamine solution, 1000 μL of hydroiodic acid and 200 μL of hypophosphorous acid solution were mixed at 50°C to obtain a colorless and clear solution 2;
[0065] A203, 198 μL of solution 1 and 198 μL of solution 2 were mixed at 50°C, followed by adding 1000 μL of 57 wt% hydroiodic acid and 200 μL of hypophosphorous acid solution, then heating to 120°C and continuing to stir until the solution became transparent, and finally cooling to room temperature to obtain a two-dimensional single crystal material;
[0066] A204, dissolve 90 mg of two-dimensional single crystal material in 2 mL of isopropanol (IPA) solution, then filter with a 0.22 μm polytetrafluoroethylene (PTFE) filter, and dilute with IPA solution 1:10 for standby use, place the ITO / ZnO conductive glass substrate in a UV ozone cleaner for 5 min, take 40 μL of the diluted two-dimensional single crystal-IPA solution and spin-coat it on the surface of the ZnO electron transport layer of the ITO / ZnO substrate at a speed of 3000 rpm / s, the spin coating time is 30 s, and obtain a two-dimensional material seed layer (B2PbI4);
[0067] A3, preparing an all-inorganic perovskite CsPbIBr2 film on the surface of the two-dimensional material seed layer to obtain an ITO / ZnO / CsPbIBr2 film;
[0068] A4. Prepare a Spiro-OMeTAD hole transport layer on the surface of the all-inorganic perovskite CsPbIBr2 film to obtain a substrate to be evaporated; specifically: dissolve 72.3 mg Spiro-OMeTAD in 1 mL chlorobenzene solution, then let it stand for 1.5 hours, then add 28.8 μL TBP, 17.5 μL lithium salt solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile) and 28.9 μL cobalt salt solution (300 mg Co(III)-TFSI dissolved in 1 mL acetonitrile), stir evenly and continue to stand for 2.5 hours, filter with a 0.22 μm PTFE filter head, drop the filtrate on the surface of the all-inorganic perovskite CsPbIBr2 film, and rotate at a speed of 5000 rpm for 30 seconds to obtain a substrate to be evaporated;
[0069] A5. Evaporate metal as an electrode on the surface of the Spiro-OMeTAD hole transport layer of the substrate to be evaporated. Specifically, put the substrate to be evaporated and the sample into the chamber, and evacuate the vacuum to 10 by the mechanical pump and molecular pump in turn. -4 Pa, first The deposition rate was then increased to 20 nm. Until the total thickness of the deposited layer is 50nm, The battery device was manufactured by evaporation at a deposition rate of until the total thickness of the deposited layer was 70 nm.
[0070] Example 2
[0071] A method for preparing an all-inorganic perovskite CsPbIBr2 film comprises the following steps:
[0072] S1. Mix and dissolve 200 mg CsI and 300 mg PbBr2 in 1 mL DMSO solution at 65 °C. After the solution cools to room temperature, filter it through a PTFE membrane with a filter diameter of 0.25 μm to obtain a completely clear CsPbIBr2 precursor solution.
[0073] S2. Spin coat 45 μL of CsPbIBr2 precursor solution on an ITO / ZnO conductive glass substrate, first at 450 rpm / s for 8 s, then at 3000 rpm / s for 50 s; anneal the spin-coated material in a nitrogen atmosphere at 35°C for 50 s, then at 170°C for 8 min to obtain an all-inorganic perovskite CsPbIBr2 thin film.
[0074] The preparation steps of all-inorganic perovskite cells are:
[0075] A1. Cleaning the ITO transparent conductive glass substrate, and then preparing a ZnO electron transport layer on the ITO transparent conductive glass substrate; specifically:
[0076] A101. Wipe the etched 16mm*16mm ITO transparent conductive glass with absorbent cotton dipped in detergent water and rinse the conductive surface. Then, place it in water, acetone, anhydrous ethanol and isopropanol for 20 minutes in sequence, blow it dry with nitrogen, and finally ultrasonicate it in ultraviolet ozone environment for 15 minutes to improve the surface wettability, so as to obtain a pretreated ITO substrate; the power of each ultrasonication is 30KHz;
[0077] A102, 120 mg Zn(CH3COO)2·2H2O and 30 μL ethanolamine were uniformly mixed in 1000 μL dimethyl glycol, and then filtered through a polyethersulfone (PES) filter with a filter diameter of 0.25 μm to obtain a ZnO precursor solution;
[0078] A103, spin coating the ZnO precursor solution on the pretreated ITO substrate at a speed of 3500 rpm / s for 25 seconds, and then annealing at 220° C. for 25 minutes to obtain an ITO / ZnO substrate;
[0079] A2. Prepare a two-dimensional single crystal material, and deposit the two-dimensional single crystal material on the surface of the ZnO electron transport layer to form a two-dimensional material seed layer; specifically:
[0080] A201, 1.5 mmol of PbO powder, 1.5 mL of 57 wt% hydroiodic acid solution and 220 μL of hypophosphorous acid solution were mixed, and then stirred at 80° C. for 35 min to obtain solution 1;
[0081] A202, 180 μL of benzylamine solution, 900 μL of hydroiodic acid and 250 μL of hypophosphorous acid solution were mixed at 45°C to obtain a colorless and clear solution 2;
[0082] A203, 180 μL of solution 1 and 180 μL of solution 2 were mixed at 55° C., and then 900 μL of 57 wt % hydroiodic acid and 250 μL of hypophosphorous acid solution were added, and then the temperature was raised to 130° C. and stirring was continued until the solution became transparent, and finally cooled to room temperature to obtain a two-dimensional single crystal material;
[0083] A204, dissolve 80 mg of two-dimensional single crystal material in 2 mL of isopropanol (IPA) solution, then filter with a 0.22 μm polytetrafluoroethylene (PTFE) filter, and dilute with IPA solution 1:10 for standby use, place the ITO / ZnO conductive glass substrate in a UV ozone cleaner for 5 min, take 40 μL of the diluted two-dimensional single crystal-IPA solution and spin-coat it on the surface of the ZnO electron transport layer of the ITO / ZnO substrate at a speed of 2500 rpm / s, the spin coating time is 35 s, and obtain a two-dimensional material seed layer (B2PbI4);
[0084] A3, preparing an all-inorganic perovskite CsPbIBr2 film on the surface of the two-dimensional material seed layer to obtain an ITO / ZnO / CsPbIBr2 film;
[0085] A4. Prepare a Spiro-OMeTAD hole transport layer on the surface of the all-inorganic perovskite CsPbIBr2 film to obtain a substrate to be evaporated; specifically: dissolve 70 mg Spiro-OMeTAD in 1 mL chlorobenzene solution, then let it stand for 1 hour, then add 25 μL TBP, 20 μL lithium salt solution (500 mg Li-TFSI dissolved in 0.5 mL acetonitrile) and 30 μL cobalt salt solution (350 mg Co (III) -TFSI dissolved in 1.5 mL acetonitrile), stir evenly and continue to stand for 3 hours, filter with a 0.22 μm PTFE filter head, drop the filtrate on the surface of the all-inorganic perovskite CsPbIBr2 film, rotate at 4500 rpm for 35 seconds to obtain a substrate to be evaporated;
[0086] A5. Evaporate metal as an electrode on the surface of the Spiro-OMeTAD hole transport layer of the substrate to be evaporated. Specifically, put the substrate to be evaporated and the sample into the chamber, and evacuate the vacuum to 10 by the mechanical pump and molecular pump in turn. -4 Pa, first 25 nm was deposited at a deposition rate of 1.5 nm and then the deposition rate was increased to Until the total thickness of the deposited layer is 45nm, The battery device was prepared by evaporation at a deposition rate of until the total thickness of the deposited layer reached 75 nm.
[0087] Example 3
[0088] A method for preparing an all-inorganic perovskite CsPbIBr2 film comprises the following steps:
[0089] S1. Mix and dissolve 300 mg CsI and 400 mg PbBr2 in 1 mL DMSO solution at 55°C. After the solution cools to room temperature, filter it through a PTFE membrane with a filter diameter of 0.2 μm to obtain a completely clear CsPbIBr2 precursor solution.
[0090] S2. Spin coat 35 μL of CsPbIBr2 precursor solution on an ITO / ZnO conductive glass substrate, first at 550 rpm / s for 3 seconds, and then at 2000 rpm / s for 70 seconds; anneal the spin-coated material in a nitrogen atmosphere at 25°C for 70 seconds, and then at 130°C for 12 minutes to obtain an all-inorganic perovskite CsPbIBr2 thin film.
[0091] The preparation steps of all-inorganic perovskite cells are:
[0092] A1. Cleaning the ITO transparent conductive glass substrate, and then preparing a ZnO electron transport layer on the ITO transparent conductive glass substrate; specifically:
[0093] A101. Wipe the etched 16mm*16mm ITO transparent conductive glass with absorbent cotton dipped in detergent water and rinse the conductive surface. Then, place it in water, acetone, anhydrous ethanol and isopropanol for 30 minutes in sequence, blow it dry with nitrogen, and finally ultrasonicate it in ultraviolet ozone environment for 25 minutes to improve the surface wettability, so as to obtain a pretreated ITO substrate; the power of each ultrasonication is 50KHz;
[0094] A102, 80 mg Zn(CH3COO)2·2H2O and 25 μL ethanolamine were uniformly mixed in 950 μL dimethyl glycol, and then filtered through a polyethersulfone (PES) filter with a filter diameter of 0.2 μm to obtain a ZnO precursor solution;
[0095] A103, spin coating the ZnO precursor solution on the pretreated ITO substrate at a speed of 4500 rpm / s for 35 seconds, and then annealing at 180° C. for 35 minutes to obtain an ITO / ZnO substrate;
[0096] A2. Prepare a two-dimensional single crystal material, and deposit the two-dimensional single crystal material on the surface of the ZnO electron transport layer to form a two-dimensional material seed layer; specifically:
[0097] A201, 0.5 mmol PbO powder, 0.5 mL of 57 wt% hydroiodic acid solution and 180 μL of hypophosphorous acid solution were mixed, and then stirred at 100° C. for 25 min to obtain solution 1;
[0098] A202, 210 μL of benzylamine solution, 1100 μL of hydroiodic acid and 150 μL of hypophosphorous acid solution were mixed at 55°C to obtain a colorless and clear solution 2;
[0099] A203, 210 μL of solution 1 and 210 μL of solution 2 were mixed at 45°C, followed by the addition of 1100 μL of 57 wt% hydroiodic acid and 150 μL of hypophosphorous acid solution, followed by heating to 110°C and stirring until the solution became transparent, and finally cooled to room temperature to obtain a two-dimensional single crystal material;
[0100] A204, dissolve 100 mg of two-dimensional single crystal material in 2 mL of isopropanol (IPA) solution, then filter with a 0.22 μm polytetrafluoroethylene (PTFE) filter, and dilute with IPA solution 1:10 for standby use, place the ITO / ZnO conductive glass substrate in a UV ozone cleaner for 5 min, take 40 μL of the diluted two-dimensional single crystal-IPA solution and spin-coat it on the surface of the ZnO electron transport layer of the ITO / ZnO substrate at a speed of 3500 rpm / s, the spin-coating time is 25 s, and obtain a two-dimensional material seed layer (B2PbI4);
[0101] A3, preparing an all-inorganic perovskite CsPbIBr2 film on the surface of the two-dimensional material seed layer to obtain an ITO / ZnO / CsPbIBr2 film;
[0102] A4. Prepare a Spiro-OMeTAD hole transport layer on the surface of the all-inorganic perovskite CsPbIBr2 film to obtain a substrate to be evaporated; specifically: dissolve 75 mg Spiro-OMeTAD in 1 mL chlorobenzene solution, then let it stand for 2 hours, then add 30 μL TBP, 15 μL lithium salt solution (550 mg Li-TFSI dissolved in 1.5 mL acetonitrile) and 25 μL cobalt salt solution (250 mg Co(III)-TFSI dissolved in 0.5 mL acetonitrile), stir evenly and continue to stand for 2 hours, filter with a 0.22 μm PTFE filter head, drop the filtrate on the surface of the all-inorganic perovskite CsPbIBr2 film, and rotate at a speed of 5500 rpm for 25 seconds to obtain a substrate to be evaporated;
[0103] A5. Evaporate metal as an electrode on the surface of the Spiro-OMeTAD hole transport layer of the substrate to be evaporated. Specifically, put the substrate to be evaporated and the sample into the chamber, and evacuate the vacuum to 10 by the mechanical pump and molecular pump in turn. -4 Pa, first 15 nm was deposited at a deposition rate of 100 nm and then the deposition rate was increased to Until the total thickness of the deposited layer is 55nm, The battery device was prepared by evaporation at a deposition rate of until the total thickness of the deposited layer was 65 nm and was named Device with B2PbI4.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 1 is that the benzylamine solution in A202 is replaced by 2-thiophenemethylamine solution to obtain a two-dimensional material seed layer T2PbI4, and the other implementation conditions are the same as those in Example 1, and finally a battery device Device with T2PbI4 is obtained.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 1 is that step A2 is omitted, and CsPbIBr2 perovskite is directly spin-coated on the ITO / ZnO substrate to obtain a traditional thin film. The remaining implementation conditions are the same as those in Example 1, and a pristine device is finally obtained.
[0108] Experimental Example 1 Performance Test of Film
[0109] 1. Taking the two-dimensional material seed layer material prepared in step A2 of Example 1 and Comparative Example 1 as an example, Figure 1 The UV-visible absorption spectra of two two-dimensional single crystals B2PbI4 (Example 1) and T2PbI4 (Comparative Example 1) are shown in FIG. Figure 2 The XRD spectra of two two-dimensional single crystals B2PbI4 (Example 1) and T2PbI4 (Comparative Example 1) are shown in Figure 2. Figure 1 and Figure 2 This indicates that the present invention has successfully produced the RP-type two-dimensional single crystal with n=1.
[0110] 2. Taking the thin film material prepared in step A3 of Example 1 and Comparative Example 2 as an example, Figure 3 Schematic diagram of the film formation process of the traditional thin film (Comparative Example 2) growth method, Figure 4 Schematic diagram of the film formation process of the two-dimensional single crystal assisted growth method (Example 1). Compared with the traditional top-down crystallization process, the two-dimensional single crystal in the method of the present invention will also induce crystallization at the buried interface, and crystallization will grow simultaneously on the upper and lower surfaces. At the same time, based on the unique orientation of the two-dimensional single crystal, the epitaxially grown perovskite lattice is more regular and orderly.
[0111] Figure 5 Quasi-in-situ XRD characterization of the traditional film growth method (Comparative Example 2) under low temperature annealing conditions. Figure 6 It is a quasi-in-situ XRD characterization of the two-dimensional single crystal assisted film growth (Example 1) under low temperature annealing. Figure 5 and Figure 6 By comparison, it was found that with the assistance of two-dimensional single crystal B2PbI4, the (110) crystal plane grew preferentially, indicating that two-dimensional single crystals can induce specific crystal planes of all-inorganic wide-bandgap perovskites.
[0112] Figure 7 and Figure 8 This shows that the overall orientation of the films obtained by the two film-forming methods is similar, but there are differences in the values of the crystal area fractions. Fig. 9In order to compare the integral ratios of the 90° (100) crystal plane, 45° (110) crystal plane, and 36.4° (111) crystal plane in each GIWAXS image, the data show that the (100) crystal plane of the perovskite film obtained by the original film formation method accounts for a high proportion, indicating that there are more internal defects; while the (100) / (110) crystal plane ratio of the perovskite film assisted by two-dimensional single crystal growth is closer to 1:1, indicating that the film has fewer crystallographic defects and is closer to the ideal lattice.
[0113] The above test results prove that the two-dimensional single crystal assisted growth of the film can obtain better perovskite films by optimizing the crystallization dynamics and crystal phase ratio.
[0114] Experimental Example 2 Battery Device Test
[0115] Taking the battery devices prepared in Example 1, Comparative Example 1 and Comparative Example 2 as examples, the devices were subjected to TPC, TPV and JV tests. The interface transport carrier transmission velocity fitting, the perovskite intrabulk phase transport carrier lifetime fitting, the carrier diffusion coefficient and the carrier diffusion length fitting are shown in Tables 1 and Figure 10-13 shown.
[0116] Table 1 Device carrier performance fitting data
[0117]
[0118] Combined with Table 1, TPC( Fig.10 )、TPV( Fig.11 ) data show that the perovskite device grown with the assistance of two-dimensional single crystal has a longer carrier lifetime and a faster interface carrier transfer rate; IMPS ( Fig.12 )、IMVS( Fig.13 ) Data show that the perovskite device grown with the assistance of two-dimensional single crystals has a larger diffusion coefficient and carrier diffusion length. A comprehensive comparison shows that the device grown with the assistance of B2PbI4 single crystals has better performance in carrier transport and is more conducive to the collection and extraction of carriers at the interface of the transport layer.
[0119] Fig.14 This is a comparison of the JV curves of devices prepared by traditional thin film growth and two-dimensional single crystal B2PbI4 assisted growth methods. The device parameters are shown in Table 2.
[0120] Table 2 Battery device performance parameters
[0121]
[0122] After assisted growth by two-dimensional single crystals, the energy conversion efficiency of the device can be increased from 10.7% to 11.8%, indicating that two-dimensional single crystals are first greatly improved in the preparation of perovskite films, and the films obtained by epitaxial growth have a more regular microstructure; in the device, it is reflected in the improvement of carrier transport performance, and ultimately the energy conversion efficiency is correspondingly improved.
Claims
1. A method for preparing an all-inorganic perovskite CsPbIBr2 thin film, characterized in that: The following steps are involved: S1, CsI and PbBr2 are mixed and dissolved in an organic solvent at a mass ratio of 200-300:300-400, and then filtered to obtain a CsPbIBr2 precursor solution; S2. Spin-coat the CsPbIBr2 precursor solution onto the substrate, followed by annealing to obtain an all-inorganic perovskite CsPbIBr2 film.
2. The method for preparing the all-inorganic perovskite CsPbIBr2 thin film according to claim 1, characterized in that: The spin coating step is: first spin coating the CsPbIBr2 precursor solution at a rotation speed of 450-550rpm / s for 3-8s, and then spin coating at a rotation speed of 2000-3000rpm / s for 50-70s.
3. The method for preparing the all-inorganic perovskite CsPbIBr2 thin film according to claim 1, characterized in that: The annealing step is: placing the spin-coated material in a protective atmosphere, first annealing at 25-35° C. for 50-70 seconds, and then annealing at 130-170° C. for 8-12 minutes to obtain an all-inorganic perovskite CsPbIBr2 film.
4. An all-inorganic perovskite CsPbIBr2 film, characterized in that: The film is prepared by the method for preparing the all-inorganic perovskite CsPbIBr2 film according to any one of claims 1 to 3.
5. Use of the all-inorganic perovskite CsPbIBr2 film according to claim 4 in the preparation of all-inorganic perovskite batteries.
6. The use according to claim 5, characterized in that: The preparation steps of the all-inorganic perovskite battery are: A1, cleaning the conductive substrate, and then preparing a ZnO electron transport layer on the conductive substrate; A2. preparing a two-dimensional single crystal material, and depositing the two-dimensional single crystal material on the surface of the ZnO electron transport layer to form a two-dimensional material seed layer; A3, preparing an all-inorganic perovskite CsPbIBr2 film on the surface of the two-dimensional material seed layer to obtain an ITO / ZnO / CsPbIBr2 film; A4, preparing a Spiro-OMeTAD hole transport layer on the surface of the all-inorganic perovskite CsPbIBr2 film to obtain a substrate to be evaporated; A5. Evaporate metal as an electrode on the surface of the Spiro-OMeTAD hole transport layer of the substrate to be evaporated to produce a battery device.
7. The use according to claim 6, characterized in that: The A1 is specifically: A101, rinse the conductive surface of the conductive substrate, then ultrasonicate in water, acetone, anhydrous ethanol and isopropanol for 20-30 minutes, then blow dry with nitrogen, and finally ultrasonicate in a UV ozone environment for 15-25 minutes to obtain a pretreated ITO substrate; the power of each ultrasonication is 30-50KHz; A102, uniformly mix Zn(CH3COO)2·2H2O and ethanolamine in dimethyl glycol, filter, and obtain a ZnO precursor solution; the ratio of Zn(CH3COO)2·2H2O, ethanolamine and dimethyl glycol is 80-120 mg: 25-30 μL: 950-1000 μL; A103. Spin-coat the ZnO precursor solution on the pretreated ITO substrate at a rotation speed of 3500-4500 rpm / s for 25-35 seconds, and then anneal at 180-220° C. for 25-35 minutes to obtain an ITO / ZnO substrate.
8. The use according to claim 6, characterized in that: The A2 is specifically: A201, PbO powder, hydroiodic acid and hypophosphorous acid solution are mixed, and then stirred at 80-100° C. for 25-35 min to obtain solution 1; the ratio of PbO powder, hydroiodic acid and hypophosphorous acid is 0.5-1.5 mmol: 0.5-1.5 mL: 180-220 μL; A202, mixing benzylamine solution, hydroiodic acid and hypophosphorous acid solution at a volume ratio of 180-210:900-1100:150-250 at 45-55° C. to obtain solution 2; A203, mixing solution 1 and solution 2 at a volume ratio of 1-2:1-2 at 45-55°C, then adding hydroiodic acid and hypophosphorous acid solution, then heating to 110-130°C and continuing to stir until the solution becomes transparent, and finally cooling to room temperature to obtain a two-dimensional single crystal material; the volume ratio of solution 1, solution 2, hydroiodic acid and hypophosphorous acid solution is 180-210:180-210:900-1100:150-250; A204. Dissolve the two-dimensional single crystal material in an organic solvent, and then spin-coat it on the surface of the ZnO electron transport layer of the ITO / ZnO substrate at a rotation speed of 2500-3500 rpm / s for 25-35s to obtain a two-dimensional material seed layer.
9. The use according to claim 6, characterized in that: The A4 is specifically as follows: 2,2',7,7'-tetrakis[N,N-diphenylamino]-9,9'-spirobifluorene is dissolved in a chlorobenzene solution, then allowed to stand for 1-2 hours, and then 4-tert-butylpyridine, a lithium salt solution and a cobalt salt solution are added, stirred evenly and allowed to stand for 2-3 hours, filtered, and the filtrate is dropwise coated on the surface of the all-inorganic perovskite CsPbIBr2 film, and rotated at a speed of 4500-5500 rpm for 25-35 seconds to obtain a substrate to be evaporated; the ratio of the Spiro-OMeTAD, TBP, lithium salt solution and cobalt salt solution is 70-75 mg: 25-30 μL: 15-20 μL: 25-30 μL.
10. The use according to claim 6, characterized in that: The A5 is specifically as follows: placing the substrate to be evaporated and the sample into the chamber, and vacuuming the chamber to 10 by the mechanical pump and the molecular pump in turn. -4 Pa, first The deposition rate was then increased to 15-25 nm. Until the total thickness of the deposited layer is 45-55nm, The deposition rate is evaporation until the total thickness of the deposited layer is 65-75nm.